2021
DOI: 10.3397/1/37691
|View full text |Cite
|
Sign up to set email alerts
|

Compact 2DOF liner based on a long elastic open-neck acoustic resonator for low frequency absorption

Abstract: Passive acoustic liners, used in aeronautic engine nacelles to reduce radiated fan noise, have a quarter-wavelength behavior. The simplest systems are SDOF-type (single degree of freedom), consisting of a perforated sheet backed with a honeycomb, whose absorption ability is limited to frequencies near the Helmholtz frequency. Thus, to widen the absorption frequency range, manufacturers use a 2DOF (double degree of freedom) system, with an internal layer over another honeycomb (stack of two resonators). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the limit where the pore radius tends to +1 (or, a bit more realistically, to 1m), the honeycomb behaves like the open ambient fluid. • A LEONAR [10,13] consists in the combination of tubes and a cavity [14,15]. The tubes are modeled similarly to a perforated plate of increased thickness, while the cavity is taken as a honeycomb layer of adequate radius.…”
Section: Acoustic Liner Modellingmentioning
confidence: 99%
“…In the limit where the pore radius tends to +1 (or, a bit more realistically, to 1m), the honeycomb behaves like the open ambient fluid. • A LEONAR [10,13] consists in the combination of tubes and a cavity [14,15]. The tubes are modeled similarly to a perforated plate of increased thickness, while the cavity is taken as a honeycomb layer of adequate radius.…”
Section: Acoustic Liner Modellingmentioning
confidence: 99%
“…Past research has shown neck extensions leading to lower-frequency sound attenuation [19][20][21][22][23], due to the introduction of multiple resonance frequencies, when the neck extensions become significantly large [24][25][26][27]. Following the recent surge in studies such as Simon et al [28] and Jones et al [29] investigating the use of extended-neck resonators for low-frequencysound absorption, this paper presents the underlying mechanism of sound attenuation from double-degree-of-freedom (2-DoF) resonators with varying neck extensions.…”
Section: Introductionmentioning
confidence: 99%